2021
DOI: 10.1108/ijchm-06-2020-0548
|View full text |Cite
|
Sign up to set email alerts
|

Are environmental-related online reviews more helpful? A big data analytics approach

Abstract: Purpose Based on more than 2.7 million online reviews (ORs) collected with big data analytical techniques from Booking.com and TripAdvisor.com, this paper aims to explore if and to what extent environmental discourse embedded in ORs has an impact on electronic word-of-mouth (e-WOM) helpfulness across eight major destination cities in North America and Europe. Design/methodology/approach This study gathered, by means of Big Data techniques, 2.7 million ORs hosted on Booking.com and TripAdvisor, and covering h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 113 publications
(247 reference statements)
0
32
0
Order By: Relevance
“…Third, when we focus on articles published in H&T outlets, the prevailing macro-topical areas are as follows: the perceptions, experiences, emotions, satisfaction and engagement with hospitality and tourism services of tourists residents and service providers (Cheng and Jin, 2019; Filieri and Mariani, 2021; Lee et al , 2019; Mariani et al , 2018; Mariani and Borghi, 2021; Park et al , 2020); demand evaluation and forecast/prediction (Höpken et al , 2020; Park and Pan, 2018; Sánchez-Medina and C-Sánchez, 2020); mapping, identification and representation of tourists, tourist behaviors, attractions, destinations and trips (Batista e Silva et al , 2018; Chun et al , 2020; Ma et al , 2020); knowledge and value creation (Kubo et al , 2020; Line et al , 2020), also in smart cities and smart ecosystems (Buhalis and Sinarta, 2019); and methodological contributions, shedding light on a specific technique or family of techniques (Alaei et al , 2019; Fu et al , 2019; Kirilenko et al , 2018), measurement problems (Khalilzadeh and Tasci, 2017), data quality issues (Xiang et al , 2017) or platform issues and features (Salas-Olmedo et al , 2018). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Third, when we focus on articles published in H&T outlets, the prevailing macro-topical areas are as follows: the perceptions, experiences, emotions, satisfaction and engagement with hospitality and tourism services of tourists residents and service providers (Cheng and Jin, 2019; Filieri and Mariani, 2021; Lee et al , 2019; Mariani et al , 2018; Mariani and Borghi, 2021; Park et al , 2020); demand evaluation and forecast/prediction (Höpken et al , 2020; Park and Pan, 2018; Sánchez-Medina and C-Sánchez, 2020); mapping, identification and representation of tourists, tourist behaviors, attractions, destinations and trips (Batista e Silva et al , 2018; Chun et al , 2020; Ma et al , 2020); knowledge and value creation (Kubo et al , 2020; Line et al , 2020), also in smart cities and smart ecosystems (Buhalis and Sinarta, 2019); and methodological contributions, shedding light on a specific technique or family of techniques (Alaei et al , 2019; Fu et al , 2019; Kirilenko et al , 2018), measurement problems (Khalilzadeh and Tasci, 2017), data quality issues (Xiang et al , 2017) or platform issues and features (Salas-Olmedo et al , 2018). …”
Section: Discussionmentioning
confidence: 99%
“…the perceptions, experiences, emotions, satisfaction and engagement with hospitality and tourism services of tourists residents and service providers (Cheng and Jin, 2019; Filieri and Mariani, 2021; Lee et al , 2019; Mariani et al , 2018; Mariani and Borghi, 2021; Park et al , 2020);…”
Section: Discussionmentioning
confidence: 99%
“…Understanding residents' engagement with environmental issues on social media may also provide a way to understand the importance of managing environmental impacts to boost ES, and guide decisions for event attendance. As Mariani and Borghi (2021) observed, online consumers' environmental discourses positively affect how they perceive electronic word-of-mouth helpfulness in hotel choice.…”
Section: Managerial Implicationsmentioning
confidence: 77%
“…Consequently, customers and residents can find it difficult to make a priori assessments of an event's environmental sustainability. Thus, environmental certification can provide an effective means for signaling environmental commitments to gain customer attention and trust while enhancing an event's reputation, both offline and online (Mariani and Borghi, 2021).…”
Section: Hypotheses Development 31 Perceptions Of Environmental Certification and Environmental Impactsmentioning
confidence: 99%
“…Despite the perhaps undeniable advantages in terms of costs and benefits of working with immense databases from online reviews (as is shown by the proliferation of such works in the hospitality field using portals, such as TripAdvisor.com and Booking.com; see e.g. Filieri et al , 2020; Mariani and Borghi, 2021), their limitations with respect to defining variables will continue to justify the need for fieldwork with small samples and longer questionnaires, the results of which could serve as a robustness check for findings. Another second, complementary future research line concerning cruise research specifically could be the use of the same e-WOM database to analyze how the ongoing complicated sailing restrictions imposed by the COVID-19 pandemic, which often turn a cruise vessel into a “big floating social bubble”, are influencing general satisfaction and cruisers’ loyalty behavior.…”
Section: Discussionmentioning
confidence: 99%